2006
DOI: 10.1093/bja/ael121
|View full text |Cite
|
Sign up to set email alerts
|

Epidural catheter placement in children: comparing a novel approach using ultrasound guidance and a standard loss-of-resistance technique

Abstract: Ultrasonography is a useful aid to verify epidural placement of local anaesthetic agents and epidural catheters in children. Advantages include a reduction in bone contacts, faster epidural placement, direct visualization of neuraxial structures and the spread of local anaesthetic inside the epidural space. Ultrasound guidance requires additional training and good manual skills, and should only be used once experience in ultrasound-guided techniques of regional anaesthesia has been acquired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 31 publications
3
107
0
Order By: Relevance
“…* tissues that allow the beam to pass easily (e.g., containing fluids or blood) create only little echo (hypoechoic) and appear black on the screen, while tissues that allows less beam to pass (e.g., fat and bone) create stronger echoes (hyperechoic) and thus appear white on the screen; * * linear transducers have a higher frequency (10)(11)(12)(13)(14)(15) and are usually used for superficial structures; curved transducers have a lower frequency (4)(5)(6)(7)(8) and are usually used for deeper structures. This paper highlights current and potential future applications of ultrasound in the field of anesthesiology.…”
Section: Figure 1: Concept Of Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…* tissues that allow the beam to pass easily (e.g., containing fluids or blood) create only little echo (hypoechoic) and appear black on the screen, while tissues that allows less beam to pass (e.g., fat and bone) create stronger echoes (hyperechoic) and thus appear white on the screen; * * linear transducers have a higher frequency (10)(11)(12)(13)(14)(15) and are usually used for superficial structures; curved transducers have a lower frequency (4)(5)(6)(7)(8) and are usually used for deeper structures. This paper highlights current and potential future applications of ultrasound in the field of anesthesiology.…”
Section: Figure 1: Concept Of Ultrasonographymentioning
confidence: 99%
“…Willschke et al [15] evaluated ultrasound guidance for epidural catheter placement in children below six years, found that ultrasonography is helpful in reducing bone contacts, faster epidural placement, and offered direct visualization of neuraxial structures and the spread of local anesthetic inside the epidural space. Again, it needs highly skilled hands.…”
Section: Neuraxial and Chronic Pain Proceduresmentioning
confidence: 99%
“…9 Although surface ultrasonography is a non-invasive tool that can be used in awake patients, its usefulness for thoracic epidural imaging is limited because of the narrow thoracic intervertebral spaces and the oblique trajectory needed for ultrasound imaging in this region. 10,11 Transesophageal echocardiography (TEE) has the theoretical potential to overcome this age-related barrier by obtaining images of spinal canal stuctures using the intervertebral disc as an acoustic window.…”
Section: Résumé Objectif Les Objectifs De Cette éTude éTaient De Détementioning
confidence: 99%
“…of these studies, 13 were excluded because they did not provide blinded assessment or sample size justification. [1][2][3][4][5][6][7][8][9][10][11][12][13] of the remaining 15 RCTs, seven compared US to traditional adjunctive modalities for peripheral nerve blocks (Table i), while eight compared stimulating to non-stimulating perineural catheters (Table ii).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%